Divergence study of rice (Oryza sativa L) genotypes for consumer-preferred quality traits - Khaire, Amrutlal R.; Singh, S. K.; Jayasudha, M.; Singh, Akanksha; Singh, D. K.; Korada, Mounika (Journal of Experimental Agriculture International, 2022)
Aim: To study the divergence of forty rice genotypes for consumer-preferred eleven quality traits. Design, Place and Duration of the Study: The rice seeds were harvested from randomly selected plants grown in alpha lattice design with three replications during Kharif season (start in June and end in October) 2018 at Agricultural research farm, Banaras Hindu University, Varanasi UP, India. Methodology: The data were analysed using biometrical tools - Mahalanobis D2 and Principal Component Analysis (PCA). The studied traits include, - grain length, grain breadth, kernel length, length to breadth ratio, kernel breadth, kernel length after cooking, kernel breadth after cooking, elongation ratio, elongation index, amylose content and alkali digestion value. Results: Using Mahalanobis D2, all forty genotypes were distributed into six clusters. The maximum inter-cluster distance was recorded between Cluster II to cluster V (5.76), followed by cluster V and cluster III (5.71), and cluster II and cluster VI (5.57) which indicated the existence of high genetic diversity among genotypes in these clusters and, therefore, crosses between the genotypes of these clusters could yield desirable transgressive isolates for desirable quality traits and the importance of the genotypes present in these clusters for exploiting heterosis for the desirable traits of these clusters. The PCA indicates that the five principal components (PC) captured almost 90% of variability present among the 40 rice genotypes. Conclusion: The genotypes belonging to Cluster II to cluster V, followed by cluster V and cluster III, and cluster II and cluster VI, can be used for making crosses as they have higher mean values for quality traits and higher inter-cluster distance for greater diversity.